Problems and Prospects of Production and Export of Indian Cotton - MAYEE, C D; CHOUDHARY, Bhagirath (Cotton Research Journal, 2021)
In the last decade cotton production scenario has undergone dramatic changes and Indian cotton has not only dominated the International production but attracted the attention of all global players in the commodity for its persistent growth. In 2015, India has emerged as the world’s largest producer of cotton outpacing the mighty China. With 4000 and odd ginning and pressing (G & P) factories, Indian textile sector has scope to expand. Technology Mission on Cotton introduced in 2002 has further boosted the cotton production, quality marketing and ginning. The cotton progress in India is dotted with technology support whenever, the yield has remained stagnant. The situation became worrisome when the cotton yields remained at 280-300 kg lint per ha for nearly 20 years and the textile industry had to depend on imports. With introduction of Bt cotton the scenario changed after 2002 when the technology was permitted for commercial use in India. Within 5 years the cotton cultivation saw a sea change as farmers adopted the new technology wholeheartedly, area increased, yields doubled, pesticide use reduced and country became a net exporter of cotton.